The Characterization and Rheological Investigation of Materials for Powder Injection Moulding / Ukwueze Bonaventure Emeka...[et al.] - Ukwueze, Bonaventure Emeka; Sulong, Abu Bakar; Muhamad, Norhamidi; Sajuri, Zainuddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Stainless steel and Zirconia have become an attractive choice of powder injection moulding (PIM) materials because of their respective excellent mechanical and thermal properties. These are often combined deliberately to produce functional graded components. The characterization and rheological investigations of the materials are thus indispensable for successful implementation of subsequent stages to the PIM process. In this investigation, the powder materials were characterized. Two feedstock with solid loadings of 68% for stainless steel (17-4PH) and 50% for 3mol% yttria stabilized zirconia (3YSZ), were prepared based on optimal loading of 3% lower than the critical value. A common binder was employed comprising of 60% palm stearin and 40% polyethylene. The rheological results for the two materials exhibited pseudo-plastic and shear thinning behaviour indicated by decrease in velocity with increasing shear rate. The results also show that a temperature of 1300C is considered appropriate for injection moulding of both feedstock.